THE CONCEPT OF BARRIER ORGAN DISEASE IN THE PATHOGENESIS OF SPONDYLOARTHRITIS - E. A. Galushko; A. V. Gordeev (Научно-практическая ревматология, 2016)
There have been now prerequisites for changing the scientific view of the etiology and pathogenesis of spondyloarthritis (SpA). An important role is assigned to the dysfunction and disintegration of the so-called barrier organs that make protection of man between his internal milieu and the environment. An update on cellular and molecular mechanisms in the pathogenesis of SpA permits rheumatologists to offer a hypothesis of the concept of barrier organ disease as a preclinical stage of the diseases included in the SpA group. There is reason to think that this process involves individual genetic and immune factors leading to damage of the superficial epithelium of the mucosal membranes and epidermis that serves as the first protective barrier for innate immunity and is in contact with huge numbers of microorganisms (a microbiome) and with the pathogen-associated molecular patterns. The microbiome may affect the preclinical phase of the disease in several ways, including those to change the composition of the microflora (dysbiosis) and to act as targets for immunological dysregulation.